الآمنون والخائفون في القرآن الكريم عند سيد قطب - عامري، عائشة محمد " محمد راتب " (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study examines the concept of the saved and secured people and the doomed ones in the worldly life and in the Hereafter as mentioned in the Holy Qur'an and as interpreted by Sayyed Qutub. This study begins with discussion of the personality of Sayyed Qutub. The study also looks into the importance of Sayyed Qutub's interpretation “Fi Zilal Al-Qur'an”, as well as clarifying his unique method in this interpretation. The study then goes through “Security” and what relates to it, by defining the terms, achievement methods, and the characteristics of safe and secured people, as with “Fear”. The researcher adopted the inductive and analytical approach by scrutinizing the words “Security” and “Fear” along with their derivatives and synonyms. This study relies mainly on Sayyed Qutub's interpretation, the linguistic dictionaries, Hadith and Tafsir books, books of the sciences of Qur'an, as well as Islamic and scientific books related to the topics of security and torment. Among the most important finding of the research is that Sayyid Qutb was interested in explaining the importance of political and religious security, and the role of every Muslim individual in achieving this security. The research looks at his interpretation of the verses that talk about state affairs, the interests of Muslims, and the legal laws related to them. The research also endeavors to clarify the characteristic of the “saved people”, and the “doomed ones” in Sayyid Qutb's interpretation.